Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae) - Gill, Anthony C.; Edwards, Alasdair J. (Zootaxa, 2006)
Lubbockichthys myersi is described from a single 38.6 mm SL specimen from Blue Hole, Guam. It is unique among pseudoplesiopines in having a very slender body (greatest body depth 15.8 % SL; body depth at dorsal-fin origin 15.3 % SL) and a higher number of vertebrae (14 + 18).